The first Japanese patient with mandibular hypoplasia, deafness, progeroid features and lipodystrophy diagnosed via POLD1 mutation detection - Okada, Asami; Kohmoto, Tomohiro; Naruto, Takuya; Yokota, Ichiro; Kotani, Yumiko; Shimada, Aki; Miyamoto, Yoko; Takahashi, Rizu; Goji, Aya; Masuda, Kiyoshi; Kagami, Shoji; Imoto, Issei (Human genome variation, 2017)
Mandibular hypoplasia, deafness, progeroid features and lipodystrophy (MDPL) syndrome is a rare autosomal dominant disorder caused by heterozygous POLD1 mutations. To date, 13 patients affected by POLD1 mutation-caused MDPL have been described. We report a clinically undiagnosed 11-year-old male who noted joint contractures at 6 years of age. Targeted exome sequencing identified a known POLD1 mutation [NM_002691.3:c.1812_1814del, p.(Ser605del)] that diagnosed him as the first Japanese/East Asian MDPL case.